Characterisation and antimicrobial activity of silver nanoparticles derived from Vascellum pratense polysaccharide extract and sodium citrate - Predrag Petrović; Danijela Kostić; Anita Klaus; Jovana Vunduk; Miomir Nikšić; Đorđe Veljović; Leo van Griensven (Journal of Engineering & Processing Management, 2018)
Silver nanoparticles (AgNPs) were synthesized by "green", cheap hydrothermal method in an autoclave using sodium citrate and Vascellum pratense polysaccharide extract as reducing and stabilizing agents. Presence of spherical AgNPs was confirmed by UV-VIS spectrophotometry and scanning electron microscopy; particle size was determined as 40 nm. Even though colloidal solution had relatively low absolute value of zeta potential(-15 mV), short term stability studies suggested a stable system, with AgNPs being stabilized by both citrate and fungal polysaccharides, as FTIR spectra confirmed. The colloidal solution showed good antimicrobial activity against both G+/G- bacteria and Candida albicans, including methicilin resistant Staphylococcus aureus (MRSA). Products containing AgNPs and fungal polysaccharides, which possess various biological activities - most important being immunostimulation - may find use in treatment of skin conditions caused by pathogens.
Keywords: Silver nanoparticles; mushroom polysaccharides; zeta potential; antimicrobial activity; MRSA